STIMULATION AND REGULATION OF PRIVATE REMITTANCES IN UKRAINE - Luhovenko , N.; Kovalenko , N. (Theory and Practice of Public Administration, 2020)
In this article modern trends of private money remittances to Ukraine have been considered. The international migration has led to the flow of financial capital into the country, which was created by migrants’ remittances, namely, the money they earned abroad to meet the social needs of the whole family. At the same time, the increase in the volume of these transfers causes a significant impact not only on the well-being of Ukrainians, but also on the macroeconomic indicators of the country itself. The structure of the volume of the private money transfers to Ukraine has been presented. The volume of private money remittances to Ukraine from the leading countries of the world has been indicated. Particular attention has been paid to the study of the impact of private money remittances on the development of the Ukrainian economy. A significant, albeit rather contradictory, factor in the intensification of labor migration processes is the financial income sent to Ukraine by working abroad citizens. Foreign remittances, which are roughly comparable to FDI, are not only one of the important items of foreign exchange earnings in Ukraine, but also a sufficiently stable source of attracting capital. The remittances have a positive impact on Ukraine’s macroeconomic stability, contribute to financing the trade deficit, fiscal consolidation and maintaining the stability of the national currency. The dynamics and the state of the volume of migrants’ remittances and the impact of these remittances on GDP have been analysed. The ways to stimulate and regulate migrants’ remittances have been developed. These ways will increase the flow of funds in the country, promote GDP growth, increase the number of small and medium-sized enterprises, which will lead to an increase in jobs in the country and improve the national well-being of citizens, as well as attract foreign direct investment. The importance to identify strategic priorities for attracting of private money remittances and improving the mechanism for regulating them has been identified.